(untitled) (Journal of Engineering, 2010)
This investigation presents an extensive experimental study on the behaviour and strength of reinforced concrete T-beams before and after strengthening by using reinforced concrete jacket. Four full scale beams were first loaded to certain levels of ultimate capacity (0, 60%, 77%, 100% of failure load). Then, after formation of cracks or failure, they were repaired by reinforced concrete jacketing method and tested again up to failure. The main objective of this study is to restore the full ultimate capacity beams failed by flexure and to strengthen the cracked beam. Also, it is aimed to investigate the effect of loading condition on beam before repair on the ultimate capacity after repair. Extensive measurements of deformations, cracking and strength were made before and after repair throughout all stages of loading.Test results showed that the repairing by reinforced jacketing can effectively restore more than 150% of the full flexural capacity of the original beam. Also reinforced jacket can effectively increase the ultimate capacity of cracked T-beam after repair up to 250%. Furthermore, the use of reinforced jacket for the cracked or failed beams is greatly improved serviceability, deformation behaviour, cracking behaviour as well as ductility of T- beams compared to those of the original beams. The ultimate flexural strength of T-beams failed by flexure and repaired by reinforced concrete jacket can accurately be predicted using conventional ultimate strength method of reinforced concrete.